Evaluation of the validated intraoperative bleeding scale in liver surgery: study protocol for a multicenter prospective study - Aparicio-López, Daniel; Asencio-Pascual, José Manuel; Blanco-Fernández, Gerardo; Cugat-Andorrá, Esteban; Gómez-Bravo, Miguel Ángel; López-Ben, Santiago; Martín-Pérez, Elena; Sabater, Luis; Ramia, José Manuel; Serradilla-Martín, Mario (Frontiers in Surgery, 2023)
Background. Surgical hemostasis has become one of the key principles in the advancement of surgery. Hemostatic agents are commonly administered in many surgical specialties, although the lack of consensus on the definition of intraoperative bleeding or of a standardized system for its classification means that often the most suitable agent is not selected. The recommendations of international organizations highlight the need for a bleeding severity scale, validated in clinical studies, that would allow the selection of the best hemostatic agent in each case. The primary objective of this study is to evaluate the VIBe scale (Validated Intraoperative Bleeding Scale) in humans. Secondary objectives are to evaluate the scale's usefulness in liver surgery; to determine the relationship between the extent of bleeding and the hemostatic agent used; and to assess the relationship between the grade of bleeding and postoperative complications.Methods. Prospective multicenter observational study including 259 liver resections that meet the inclusion criteria: patients scheduled for liver surgery at one of 10 medium-high volume Spanish HPB centers using an open or minimally invasive approach (robotic/laparoscopic/hybrid), regardless of diagnosis, ASA score < 4, age ≥ 18, and who provide signed informed consent during the study period (September 2023 until the required sample size has been recruited). The participating researchers will be responsible for collecting the data and for reporting them to the study coordinators.Discussion. This study will allow us to evaluate the VIBe scale for intraoperative bleeding in humans, with a view to its subsequent incorporation in daily clinical practice.Trial Registration: This study has been registered in ClinicalTrials.gov (NCT0536998). Available at: https://clinicaltrials.gov/ct2/show/NCT05369988?term=serradilla&draw=2&rank=3.Registration date: May 2022.